Effect of b-learning in a higher education course - Carvalho, P. (2021)
Changes adopted in teaching and learning methodologies, on all teaching levels and on higher education in particular, because of the pandemic crisis triggered in March 2020, have defined development vectors worth to preserve. The use of already known Learning Management Systems became more important and, at the same time, a democratization of new technological and communication tools occurred, allowing a broader vision of a more open teaching, in line with the modernization of society. It is well known that distance teaching allows new targets in Higher Education and the democratization of education in a sense that each person can learn in his way and at his own speed. The current digital transformation, not just in education but in society in general, combined with STEAM programs, through interfaces for formal and informal education, foresees a change that we expect to be long term and beneficial. In this article, we describe a restructuration of a methodology used in a calculus course for engineering, with a large number of students (103) based on active learning and flipped classroom, centering learning in the student, in a b-learning environment. Although an intensive workflow for the teacher, which is a negative effect attributed to this approach, the described experience is based on clean and simple course design, with the possibility of reusing produced materials in the future, which softens that effect. The results of this experiment have been measured by a qualitative survey and by the learning outcomes observed in the course. Conclusions show the process is robust, can be sustained in future editions of this course, and can be adopted in similar courses of sciences and engineering.